Prevention of Violence and Bullying Againts Women: Islamic Perspectives at Muhammadiyah Islamic College Singapore - Billah, Muktashim; Abidin, Zainal; Kahar, Andi Satrianingsih; Hamzah, Nur Asia; Jamal, Mukhlisah; Amin, Saifuddin (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Violence against women remains a critical global issue, fueled by patriarchal norms and socioeconomic pressures. This study examines an Islamic-based educational outreach at Muhammadiyah Islamic College Singapore, aimed at raising awareness and offering strategies to prevent violence and bullying against women. Using a Community-Based Participatory Research (CBPR) approach, the program involved workshops, focus groups, and modules grounded in Islamic principles of justice and compassion. Findings show increased awareness among participants about respecting women's rights and maintaining a violence-free environment. The integration of Islamic values, such as emotional regulation and peaceful conflict resolution, positively influenced attitudes and behaviors. Ultimately, the program succeeded in fostering a supportive, safe campus environment, demonstrating the potential of faith-based approaches in addressing social issues and promoting inclusive communities.